Compliance evaluation of dental students in orthodontic clinic towards patient safety: observational study - Wilam, Christiana; Harsanti, Andriani; Prisinda, Diani; Malinda, Yuti; Suciati, Ame (Padjadjaran Journal of Dental Researchers and Students, 2023)
ABSTRACTIntroduction: Orthodontic clinic Universitas Padjadjaran Dental Hospital (RSGM Unpad) is an outpatient unit that provides services and treatment for malocclusion as one of the five biggest diseases at RSGM Unpad in 2021. Improving the quality of services at the orthodontic clinic by implementing patient safety standards need to be done to improve public health. The purpose of this study was to evaluate the compliance of dental students in orthodontic clinic RSGM Unpad towards patient safety. Methods: The type of research used was descriptive observational research with a purposive sampling technique and a total sample of 87 health workers was obtained. The data collection technique was carried out by observing and evaluating 87 health workers at the Orthodontic Polyclinic of RSGM Unpad in March - April 2022 using an assessment rubric. Results: The results of six quality indicators to determine compliance towards patient safety are: Patient identification compliance is 31.03%; Outpatient waiting time is 30 minutes; National formulary compliance cannot be determined; (4) Hand hygiene compliance is 12.64%; Clinical pathway compliance is 83.33%; Personal Protective Equipment compliance is 13.79%. Conclusion: Compliance evaluation of dental students in orthodontic clinic RSGM Unpad towards patient safety for outpatient waiting time compliance is compliant, and for patient identification compliance, hand hygiene compliance, clinical pathway compliance and Personal Protective Equipment compliance are non-compliant, while compliance with the use of the national formulary cannot be determined.KEY WORDS: compliance, dental students, patient safety, orthodontic clinicEvaluasi kepatuhan peserta didik klinik ortodonti terhadap keselamatan pasien: studi observasionalABSTRAK     Pendahuluan: Poliklinik ortodonti Rumah Sakit Gigi dan Mulut Universitas Padjadjaran (RSGM Unpad) merupakan unit rawat jalan yang menyediakan pelayanan dan perawatan maloklusi sebagai salah satu dari lima penyakit terbesar di RSGM Unpad pada tahun 2021. Peningkatan mutu pelayanan di poliklinik ortodonti dengan cara menerapkan standar keselamatan pasien perlu dilakukan untuk meningkatkan derajat kesehatan masyarakat. Tujuan dari penelitian ini untuk mengevaluasi kepatuhan tenaga kesehatan terhadap keselamatan pasien di poliklinik ortodonti Rumah Sakit Gigi dan Mulut Universitas Padjadjaran. Metode: Jenis penelitian yang digunakan adalah penelitian observasional deskriptif dengan teknik purposive sampling dan didapatkan jumlah sampel sebanyak 87 tenaga kesehatan. Teknik pengumpulan data dilakukan dengan melakukan pengamatan dan penilaian terhadap 87 tenaga kesehatan di Poliklinik Ortodonti RSGM Unpad pada bulan Maret – April tahun 2022 menggunakan rubrik penilaian. Hasil: Hasil dari enam indikator mutu untuk mengetahui kepatuhan terhadap keselamatan pasien adalah sebagai berikut: Kepatuhan identifikasi pasien sebesar 31,03%; Waktu tunggu rawat jalan sebesar 30 menit; Kepatuhan penggunaan formularium nasional yang tidak dapat ditentukan kepatuhannya; Kepatuhan kebersihan tangan sebesar 12,64%; Kepatuhan terhadap clinical pathway sebesar 83,33%; Kepatuhan terhadap penggunaan APD sebesar 13,79%. Simpulan: Evaluasi kepatuhan tenaga kesehatan terhadap keselamatan pasien di poliklinik ortodonti RSGM Unpad pada indikator kepatuhan waktu tunggu rawat jalan adalah patuh dan pada indikator kepatuhan identifikasi pasien, kepatuhan kebersihan tangan, kepatuhan terhadap clinical pathway dan kepatuhan penggunaan APD adalah tidak patuh, sedangkan kepatuhan penggunaan formularium nasional tidak dapat ditentukan.KATA KUNCI: kepatuhan, tenaga kesehatan, keselamatan pasien, pelayanan ortodonti